Blink & Co / Azuwina Aina Azmi and Siti Nur Aisyah Dahari Mohd - Azmi, Azuwina Aina; Dahari Mohd, Siti Nur Aisyah (2023)
BLINK & CO. was founded in March 2023 by two independent women, Azuwina Aina Binti Azmi and Siti Nur Aisyah Binti Dahari Mohd. This business is our first baby. BLINK & CO. is a partnership business that focuses on high-quality accessories and sparkling brooches that will complete the look of modest women. BLINK AND CO. is available in 20-piece brooches for RM10. We only offer the best and highest quality brooches to our customers at a cheaper price. In fact, our beloved customers may choose from an extensive selection of designs, sizes, and colours. BLINK & CO. is located at Kampung Merbau Sempak, Sungai Buloh, and covers the areas of Sungai Buloh, Puncak Alam, Subang Jaya, and also Petaling Jaya. Customers can buy directly from us or via our Facebook page, and we will deliver it to their doorstep. BLINK & CO. is very concerned about the quality of the brooches and gives only the best to our customers. In a nutshell, customers’ happiness and satisfaction are the main reasons why we are here today.